Perception and Practices of Nomadic Women in a Rural Community in Southwestern Nigeria to Their Children’s Oral Health (2017)
Nomads move from one settlement to another, thus it has been difficult to have adequate documentation about their oral health and that of their children. To investigate the perception and practices of nomadic Fulani women toward their children’s oral health. A cross-sectional study was conducted among 197 Fulani women using a structured interviewer administered questionnaire. Perceived causes of tooth decay included tooth germs/worms (23.9%) and sugar (5.1%), and 32.0%, 15.2%, and 5.1%, respectively, self-medicated children with antibiotics, traditional concoctions/herbs, and analgesics for tooth decay. Two fifths (40.1%) attributed bleeding gums to tooth germs/worms. Polyurethane foam (46.7%), toothbrush (32.0%), finger (18.8%), and wooden twigs (2.5%) were aids used for cleaning children’s teeth. These mothers have suboptimal oral health knowledge, attitudes, and practices toward their children’s oral health. There is a need for urgent intervention among this group of people.